VIRTUAL INTERACTION IN ONLINE ISLAMIC RECITATION - Rafika Hani; Syerli Haryati (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Covid 19 Pandemic restricts public sphere, and make a significant change in every sector of society life. Also in religious activity, include recitation activity for Moslem people. Since public restriction policy applied in Jakarta by the government, Majelis Taklim (MT) Tazkiyatun Nafs transform the recitation acktivity in to virtual sphere by using zoom application. The communication pattern also changes in to virtual interaction which meaning trough some process. The process consists of perception, role taking, and meaning of symbols in online recitation. This research uses qualitative approach with netnography method. The techniques of this research consist of file data, elicited data, dan field note. The results are perception process based on the interpretation of spiritual need and pandemic situation influence the action to participated in online recitation. The role taking reflected based on the participant interpretation in social structure. The meaning of symbols process influenced by role taking. For communicator the process occurred inside and outside virtual room, while for communicant the process occurred outside the virtual room.